IMPLEMENTASI PERATURAN BUPATI GOWA NOMOR 5 TAHUN 2023 TENTANG PERCEPATAN PENURUNAN STUNTING STUDI DI KABUPATEN GOWA PROVINSI SULAWESI SELATAN - Salewangang, Syamsu; Hardian, Dafyar Eliadi; Darmojo, Hardjito S. (Perspektif : Jurnal Ilmu Administrasi, 2025)
This study, entitled "Implementation of Gowa Regent Regulation Number 5 of 2023 concerning the Acceleration of Stunting Reduction," was conducted in Gowa Regency, South Sulawesi, involving the Gowa Regency Stunting Reduction Acceleration Team (TPPS) as informants, including primary informants, key informants, and supporting informants. The purpose of this study is to answer the following questions: 1) How is communication implemented in Regent Regulation Number 5 of 2023? 2) What are the resources used in implementing Regent Regulation Number 5 of 2023? 3) What is the disposition of implementing Regent Regulation Number 5 of 2023? 4) What is the bureaucratic structure used in implementing Regent Regulation Number 5 of 2023? This study used qualitative research methods. Regarding the communication aspect (transmission, clarity, and consistency), five important factors were identified that contributed to the program's success: 1) communication strategy, 2) communication actors, 3) communication activities, 4) communication materials packaged in Makassarese, and 5) communication channels. In this communication aspect, there is also innovation in conveying messages about stunting prevention using the Makassar language with the tagline Gassing Nganre. From the assessment of the resource aspect in the implementation of Gowa Regent Regulation Number 5 of 2023, it can be concluded that resource allocation has been effective with the support of sufficient and competent staff, utilization of social and institutional resources, availability of sufficient communication materials and SOPs, and adequate support facilities. In this resource aspect, there are also social/institutional and cultural resources, economic resources, and technological resources, which have great potential in implementing the acceleration of stunting reduction. Findings on the disposition aspect have not received maximum support from the Gowa Regency Government, especially in the incentives section. Meanwhile, the appointment of bureaucrats is very adequate with the existence of Gowa Regent Decree Number 131/II/2022 concerning the Formation of the Stunting Reduction Acceleration Team in Gowa Regency. Meanwhile, the bureaucratic system aspect consisting of SOPs and fragmentation implemented in the implementation of the stunting reduction acceleration program in Gowa Regency is considered quite effective due to collaboration and coordination from leaders to staff, as well as among fellow staff from across government work units. Continuity and simultaneous steps to achieve common goals will only be achieved if the bureaucratic system works effectively under the direction of effective leadership. The maximum efforts undertaken by the Stunting Reduction Acceleration Team (TPPS) in Gowa Regency have ultimately yielded a significant impact, reducing the prevalence of stunting in Gowa Regency to 17% in 2024 from 21.1% in 2023. Keywords: Gowa Regent Regulation Number 5 of 2023, Policy Implementation, Accelerating Stunting Reduction.